Ultrasound combined with DSA-guided pulsed radiofrequency for perineal herpes zoster pain management: clinical outcomes and complications - Dong, Qing-Peng; Li, Shao-Jun (Frontiers in Medicine, 2024)
Background Herpes zoster (HZ) in the perineal area is a rare disease. There are limited treatment options for this disease. This study aimed to assess the efficacy of ultrasound combined with digital subtraction angiography (DSA)-guided pulsed radiofrequency (PRF) for perineal herpes zoster-related pain. Methods Two hundred and twelve patients with perineal HZ were enrolled at the pain department. From January 1, 2018 to December 30, 2019, patients with HZ in the perineal area were treated with PRF under DSA guidance, and from January 1, 2020 to October 30, 2023, patients with HZ in the perineal area were treated with PRF under ultrasound combined with DSA guidance. The included patients were divided into two groups: DSA group and ultrasound + DSA group. The visual analogue scale (VAS), central sensitization inventory (CSI), sleep quality scores (SQS), the 36-Item Short Form Health Survey questionnaire (SF-36) at baseline and after the PRF treatment were analyzed to evaluate clinical efficacy. Results The mean VAS scores, CSI scores, SQS, and SF-36 scores were statistically significantly lower after treatment compared to baseline (p <0.001). There was no significant change in VAS scores, CSI scores, SQS, and SF-36 scores between the DSA group and the ultrasound + DSA group (p >0.05). The time it took from the start of the puncture to the successful puncture was significantly shorter in the ultrasound + DSA group compared to the DSA group (41.2±21.2 vs 48.1±20.3, p=0.035). The ultrasound + DSA group had a higher percentage of satisfaction with the procedure than the DSA group (90/99,90.9% vs 62/78,79.5%, p=0.030). A total of 27 postoperative complications occurred. The incidence of puncture site hematoma was significantly higher in the DSA group (10/78, 12.8%) than that in the ultrasound + DSA group (4/99, 4.0%) (p=0.032). Conclusion PRF can reduce pain from HZ in the perineal region, alleviate central sensitization, enhance sleep quality, and improve overall quality of life. When PRF is performed under ultrasound guidance combined with DSA, it shortens the puncture time and reduces the risk of hematoma formation at the puncture site, making it the recommended method for clinical use.